The Application of "Uno Mathematics" Game Method on Fraction Numbers - Indah Suciati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
The fraction number is a subset of the set of real numbers. Although simple and often used, this material is still quite complicated for students. To solve this problem, a solution is given in the form of the game method "Uno Mathematics". "Uno Mathematics" is an effective, interesting, and interactive way to present students to build and strengthen mastery and understanding of mathematical concepts in the long term. The steps for the game method "Uno Mathematics", namely: (1) reviewing the number of game cards as much as 48 pieces, (2) explaining the "Uno Math" game procedure and the rules of lowering the cards, (3) grouping students in groups, (4 ) give a set of “Uno Mathematics” cards to each group, (5) remind students, and (6) start the game.